2014
DOI: 10.1002/nau.22692
|View full text |Cite
|
Sign up to set email alerts
|

Influence of animal husbandry practices on void spot assay outcomes in C57BL/6J male mice

Abstract: Aims Mice are increasingly being used as models to investigate aspects of urinary dysfunction that humans with lower urinary tract symptoms (LUTS) experience. One method used to examine voiding function is the spontaneous void spot assay. The purpose of this study was to characterize and identify animal husbandry conditions that might confound results of the spontaneous void spot assay in male C57Bl/6J mice. Methods Mice were placed in cages lined with filter paper for four hours and urine was visualized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…However, as with all studies entailing live animals, technical factors can substantially affect results. We have recently reported that husbandry factors, including time of day of testing, cage changes within 24 h of testing, as well as age and body weight, significantly affected the results of VSA conducted with male C57BL/6J mice (15). However, we also observed that repeated testing of male mice over 3 consecutive days produced nearly identical results, particularly when testing was consistently performed at the same time of day (e.g., morning, afternoon, or night) (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as with all studies entailing live animals, technical factors can substantially affect results. We have recently reported that husbandry factors, including time of day of testing, cage changes within 24 h of testing, as well as age and body weight, significantly affected the results of VSA conducted with male C57BL/6J mice (15). However, we also observed that repeated testing of male mice over 3 consecutive days produced nearly identical results, particularly when testing was consistently performed at the same time of day (e.g., morning, afternoon, or night) (15).…”
Section: Discussionmentioning
confidence: 99%
“…All protocols conformed to the National Institutes of Health Guide for the Care and Use of Laboratory Animals. VSA Standardized procedures were followed to mimic those used in a previous study (31) and to minimize the impact of husbandry on results (15). Mice were allowed free access to water until placed in cages for testing.…”
Section: Micementioning
confidence: 99%
“…Void spot assays were conducted at 6 (before TϩE2 implant), 10, and 14 wk of age and analyzed as described previously (18,39). Mice were placed in a clean empty cage lined with 3MM Whatman filter paper (057163W, Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Assays were conducted in the same quiet location and time of day unless indicated otherwise. Filter papers were imaged using UV light on a transilluminator and analyzed using Image J Software (Version 1.46r) as described previously (18). Spot number, total urine area, spot size, area within the primary (largest) void, % total urine area in primary void, % total area in the corner of the paper, and % total area in the center of the paper were analyzed as described previously (18,39).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation